KEKUATAN PEMBUKTIAN AKTA NOTARIIL BERBAHASA ASING DALAM PENYELESAIAN SENGKETA WANPRESTASI - Ratih Wibisono (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT  Notarial Deed is made to ensure the certainty, order and size of law in performing legal action that serves as a written evidence of the circumstances, events or legal acts. Notarial Deed is an official document issued by a Notary who possesses absolute and binding powers of evidence, otherwise it is a perfect proof so that there is no need to be proved with other verification as untruths can not be proven. Terms of use of language in the deed, notarial deed must use indonesian language pursuant to the provisions as regulated in Article 43 paragraph (1) of Law Number 2 Year 2014 amendment to Law Number 30 Year 2004 regarding Position of Notary Indonesian Notary must be made in Bahasa Indonesia , Shall be in the hands of article 43 paragraph (3) of Law Number 2 Year 2014 on Notary Public Notary's office may be made by using a foreign language to accommodate the parties who want. In the case of translation of this deed is very possible there is a difference in the arrangement of the contents of the deed between the Indonesian language deed with a foreign language deed of the things that arise legal issues regarding the power of the Creation of the deed using foreign languages in the event of a breach event there is a difference of translation of the contents of the deed between the deed of which language Indonesia by a foreign language deed and the settlement of the legal case and how the notary's accountability as the making of the deed to the loser.